Pengaruh Kualitas Audit, Debt Default (Kegagalan Hutang) dan Ukuran Perusahaan terhadap Penerimaan Opini Audit Going Concern pada Subsektor Perusahaan Tekstil & Garment Yang Terdaftar Di Bursa Efek Indonesia pada Periode 2014-2017 - Irene Chandra; Steven Cianata; Namira Ufrida Rahmi; Fansra Septiman Zai; Alvina Alvina; Maisara Batubara (Politeknik Ganesha Medan, 2019)
Going concern audit opinion is an audit opinion with an explanatory paragraph regarding an auditor consideration that has an inability or significant uncertainty on operating a company life sustainability in the future time. There are many factors that affect going concern audit opinion which are Audit Quality, Debt Default, and Firm Size. The purpose of this research is to examine and to analyze the effect of Audit Quality, Debt Default, and Firm Size toward Revenues Going Concern Audit Opinion on the company subsector of textile and garment listed on the Indonesia Stock Exchange in 2014-2017. The types of data collections are descriptive statistics with a quantitative approach. The method of collective data used documentation study and logistic regression analysis. Using the population-based on the financial statement of textile and garment companies that are listed on the Indonesia Stock Exchange in 2014-2017. The technique which used for sampling is purposive sampling method. The result of this study showed that Audit Quality, Debt Default, and Firm Size have the simultant effect of Revenues Going Concern Audit Opinion with a significant value 0.010 < 0.05. Audit Quality and Firm Size did not affect Revenues Going Concern Audit Opinion partially. Debt Default effect the Revenues Going Concern Audit Opinion